The Authenticity of Hooker's Book VII - Woodhouse, H. F. (Church history, 1953)
This year marks the fourth centenary of Richard Hooker, who is perhaps the greatest apologist of the Anglican Church. It is easy to forget this because the epithet “judicious” when used of him conveys to most of us the idea of one who was careful, conscientious and not likely to accept or adopt rash views. But the meaning of the word “judicious” as applied to Hooker is “judicial.” It was used of one who had spoken the last word on a subject, one whose conclusions and opinion were so firmly based that neither premise nor conclusions could be shaken.